Analysis The Influence of PM Leadership Styles to Project Success Achievements (Case Study at PT. Pertamina Hulu Energy Offshore North West Java) - Kusumah, Ardiansyah; Bangun, Yuni Ros (The Indonesian Journal of Business Administration, 2015)
Abstract - Project Manager has key role and responsibilities to take charge and lead the project to ensure safe and successful execution of the project as designed (scope), meeting targets for HSSE (Health, Safety, Security, and Environment), cost, schedule and quality. Project Manager also serves as internal and external interface for the project team, coordinate staffing and ensure all key deliverables are done correctly.Leadership is an important component in helping the organization achieve its vision and mission, it is one of key success of the organization to answer the current and future problems, issues and challenges. The PM leadership style analysis will use managerial grid (9x9cell) model developed by Robert Blake and Jane Mouton depicts the five (5) leadership styles with varying concerns for people and project/production as follow: impoverished, country club, middle of road, authoritarian and team style. The project success achievements will use PHE ONWJâ€™s success criteria in term of HSSE, Scope, Schedule, Cost, and Quality.Â This research will analyze the influence each PM leadership style to each project success achievements.Keyword: Project Manager, Leadership Styles, Project Success Achievements